Pengaruh Rasio Hutang terhadap Ekuitas, Rasio Saat Ini, Rasio Cepat, Peralihan Aset dan Pengembalian Aset terhadap Pertumbuhan Laba pada Perusahaan Manufaktur Sektor Industri Dasar Kimia - Mayang Puspitasari; Muhammad Nuur Farid Thoha (Penerbit Goodwood, 2021)
Purpose: This study aimed to ascertain the impact of debt-to-equity ratio, current ratio, quick ratio, total asset turnover, and return on assets on profit growth in basic industrial and chemical manufacturing companies listed on the Indonesian Stock Exchange from 2013 to 2017. Research Methodology: The population of this study consists of 69 firms, 52 of which passed the sample selection criterion using a purposive sampling technique. The data sources for this study are the financial statements of the companies sampled via www.idx.co.id. This study employs multiple linear regression analysis and is conducted using the SPSS software version 20. (Statistical Product and Service Solutions). Results: The results of this study indicate that ROA has an impact on profit growth, while the current ratio, quick ratio, total asset turnover, and debt to equity ratios do not.